ETIKA SOSIAL GUS DUR - Abdus Salam (Refleksi Jurnal Filsafat dan Pemikiran Islam, 2014)
Islam as a complete religion that actually provides a view and the right way oflife. Yet in the reality Muslim often ignores to see social problems that continue to occur. This is seen from the lack of attention in Islam on the problem of poverty and oppression. Islam only appears in the form of individual mistake that escapist. Whereas, the Qur'an has clearly explained the concern very beautiful, as in QS. al-Baqarah [2]: 177. Therefore, it is important to re-read the meaning oflslam  by more open and critical approach, one of them through discourse ethics, which in Islam is known as "akhlak" terms. Through the theological-philosophical approach, by tracing the motives of social ethicsin the thought of Abdurrahman Wahid, who understand (through indigenization of lslam) Islamic teaching (tauhid) critically in order to realize "social pillar", this research aims to probe again the akhlak relevance (Islam) in the context of humanitarianism and Indonesian culture to answer any real-life problem for the realization of social welfare.